Deactivation and regeneration of Pt/Al2O3 catalysts during the hydrodechlorination of carbon tetrachloride - Garetto, Teresita Francisca (2009)
Deactivation and regeneration of Pt/Al2O3 catalysts during the hydrodechlorination of carbon tetrachloride were studied. The effect of reactant partial pressures and temperature on the catalyst deactivation was investigated. A deactivation model with residual activity was developed to quantify the kinetic deactivation parameters. The effect of the regeneration atmosphere was also investigated. Regeneration under air allowed for the full recovery of the catalytic performance of fresh catalysts while treatments under flowing hydrogen resulted in a superior catalytic performance, increasing both the initial and residual activities. This was ascribed to a combined effect, redispersion of the metallic phase and formation of surface defects.